U.S COLLEGE STUDENTS’ PERSPECTIVES ON INFORMAL LEARNING OF VALUES IN A CO-OP - Kim, Jae (My University, 2019)
The qualitative study is about the informal learning of values among U.S. college students living in a co-operative house called Casa Zimbabwe (CZ). The researcher uses Vygotsky’s and Engestrom’s sociocultural learning theory to delineate the transfer of values within the community of college students, and contrast the explicit values in the house bylaws and the implicit values in the interviews. The key values that the researcher focuses on are Community, Solidarity, Democracy, Equality, Equity, Liberty, Safety, Efficiency, Self-responsibility, Self-help, and Habitability. To identify these values within the community, the researcher tallied the frequency of these values described in the CZ house bylaws and interviews using the content analysis method. The two analyses were compared to each other to identify what the explicit and implicit values were among the college students. The results showed that the students living in CZ explicitly valued Community, Solidarity, Efficiency, and Self-responsibility, but implicitly valued Solidarity, Community, Democracy, and Liberty in the interviews. Furthermore, the results showed that positive and indirect reinforcements in the rules (e.g., general vs. specific bylaws), mediating tools (e.g., workshops, council, parties, and murals), division of labor (e.g., managerial vs. non-managerial workshifts), and objectives (e.g., co-operative living vs. party house) influenced the difference. This contrast was also reflective of one of the major issues with the co-operative model; it may be too idealistic and inefficient to be sustainable in the long-term.
Keywords: Qualitative Research, College Students, United States, Informal Learning, Explicit Values, Implicit Values, Co-operative Housing